The Categories of Utterances Used by Male and Female Teachers - Maharani . Dalimunthe; Anni Holila Pulungan; Zainuddin . . (LINGUISTIK TERAPAN, 2021)
This study focus on investigating utterances used by male and female teachers in teaching learning process based on inquiry model. It is a qualitative research design. The subjects were six teachers in SMP AL-Wasliyah 29 Medan. There are three male teachers and three female teachers. The data of this research is collected by recording, transcribing and analysing. Recording was applied to record utterances of male and female teachers in teaching learning process based inquiry model. Transcribing was applied to transcribe the utterances of male and female in teaching learning process based on inquiry model. And analysing was to analyse the utterances of male and female in teaching learning process based on inquiry model. The study proposed by Tanen’s theory. The problem of the study are how the categories of male and female teachers’ utterances realized and why realized in the ways they are. The data were analysed by using Miles and Huberman. The result of this study revealed that: Male and female teachers were different in delivering their utterances. It could be seen from the categories showed on their utterances. Male teachers showed the categories of male utterances, such as support, intimacy, understanding, feeling, and proposal in their utterances to their students. While female teachers showed status, advice, and orders.Keywords: Gender Differences, Inquiry Model, Teaching Learning Process, Male and Female